Análise dos indicadores de empreendedorismo e índices macroeconômicos dos países que compõem o grupo BRICS: Brasil, Rússia, Índia, China e África do Sul - Andrade, Fernanda Beazi de (2019)
Public policy choices reflect the stage of economic development of a country or region. Structural norms and actions that balance social, economic and political relations provide parameters for people seeking information on investment decision-making, job change, risk taking or not. Thus understanding and analyzing the behavior of macroeconomic indicators such as GDP per capita, inflation rate, unemployment rate and HDI, allows the optimization in the choice of public policies. For this economic dynamic, entrepreneurship has become essential, raising people's income through the production and supply of goods and services. The research proposal is aimed at understanding the relationship between macroeconomic indicators and entrepreneurship indices. In the coming years, the countries that make up the BRICS group - Brazil, Russia, India, China and South Africa, tend to be the main force of the global economy. The main objective of the study is to identify and analyze the relationship between entrepreneurship indicators and macroeconomic indices of the countries that make up the BRICS group, using descriptive, comparative statistics techniques and regression models to describe the behavior of the variables. The results were different in different economies, due to the peculiarities of each country. This is also due to the fact that entrepreneurship and macroeconomics cannot be explained in isolation, as they are influenced by many internal and external factors. The study produced important results for understanding the countries' economic situation, short-term trends, and serves as a basis for future decision-making by public and private actors through knowledge and interpretation of indicators of economic activities, and how these indicators may be linked together.